Frosting and defrosting assessment of carbon fiber reinforced polymer composite with surface wettability and resistive heating characteristics. (April 2021) - Abbas, Saleem; Park, Chan Woo
Highlights: Frosting and defrosting of CFRP was investigated. Hydrophilic, bare, and hydrophobic CFRP samples were prepared. Surface wettability and inclination angle was studied for frosting and defrosting. Resistive heating was evaluated for the defrosting performance of CFRP samples. Abstract: The thermal performance of air source heat pump (ASHP) is considerably affected by frost formation due to fin gap blockage and increased thermal resistance. Carbon fiber reinforced polymer composites (CFRP) have emerged as potential materials that can be used to fabricate lightweight polymer-based fins for ASHP. For practical application, the frosting and defrosting performance of CFRP should be investigated in terms of their effective resistive heating characteristics. Therefore, a sample CFRP fin was used to experimentally investigate its frosting and defrosting behavior corresponding to its inclination angle, applied heat flux, and surface wettability. This experiment helped understand the CFRP thermal performance under extreme winter conditions. The results demonstrated that the frost thickness increased while the density of frost decreased at higher inclination angles. For the surface-treated samples, frost thickness was highest for the bare CFRP sample, followed by hydrophobic and hydrophilic samples. For the defrosting experiment of vertical bare sample, the water retention ratio decreased with an increase in heat flux and inclination angle. For the surface-treated samples, the retention ratio was lowest for the hydrophobic sample due to surface wettability and highest for the bare sample. The hydrophobic sample exhibited the lowest time for dry-out for defrosting.